2013
DOI: 10.1080/17533015.2013.826260
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities, the arts and public health: Towards an international conversation

Abstract: This paper considers how participatory arts informed by thinking in public health can play a significant part internationally in addressing inequalities in health. It looks beyond national overviews of arts and health to consider what would make for meaningful international practice, citing recent initiatives of national networks in English-speaking countries and examples of influential developments in South America and the European Union. In the context of public health thinking on inequalities and social jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…It is artistic imagination that is liberated through these exercises and this is what can challenge existing systems that are no longer serving (Bishop, 2012). It is this re-imagining that those charged in improving public health need to consider in facilitating healthy communal and civic engagement (Parkinson & White, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is artistic imagination that is liberated through these exercises and this is what can challenge existing systems that are no longer serving (Bishop, 2012). It is this re-imagining that those charged in improving public health need to consider in facilitating healthy communal and civic engagement (Parkinson & White, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As Parkinson and White (2013) write, we must not stifle arts based research "by only seeking a proven evidence base that is narrowly defined through experimental and control designs" (p. 186). Furthermore, creative activities that can influence policy and wider public understanding need to be fostered.…”
mentioning
confidence: 98%
“…Research has shown that using music, literature, performance, drama and the visual arts has had demonstrable positive therapeutic outcomes; this applies to both physical and mental health problems (NEF 2009;White 2009;Spandler et al 2007;Staricoff 2004;Stickley 2010;RSPH 2013;Wolf and Wolf 2011;ACE 2012;Jensen 2013). This research also shows an application of not only art participation but also access to arts and culture in a variety of health care settings in Britain, Ireland, Australia, Canada, Norway, Sweden, Brazil, Peru, Finland, the Republic of Lithuania and the United States (Sonke et al 2009;Wikoff 2004;White 2009;ACI 2010;Likanen 2010;Cuypers et al 2011;Parkinson and White 2013;Tellnes 2009;Austin 2014). The positive outcomes from these initiatives have supported developing trends over the past two decades of using the arts in the wider health sector.…”
Section: Background and Contextmentioning
confidence: 95%
“…In this study, account was taken of individual-level socioeconomic factors, but it nonetheless remains to be studied whether country-level investments in culture might add to the social capital of all or only benefit some population groups that are already privileged and equipped with capacities for social participation. In several countries, Finland included, new forms of collaboration between sectors of society have been undertaken to add to everybody's right to participate in the cultural life of the community for their health and well-being (Liikanen 2010;Parkinson and White 2013).…”
Section: Discussionmentioning
confidence: 99%